Rancang Bangun Aplikasi Pengadaan Persediaan Bahan Baku Produksi Pada UMKM Sablon Garment Surabaya - Devy Wulandari; Vivine Nurcahyawati; Tony Soebijono (Jurnal Sistem Informasi Universitas Dinamika, 2017)
The production of raw materials is an important component in the Sablon Garment Surabaya for the smooth operation of production is highly dependent on the existence of raw materials. Therefore, the state of production of raw material in the warehouse Sablon Garment Prints must be really well-run, so that data ordering, receiving, and expenditures can be stored safely. Current conditions in the warehouse Sablon Garment Surabaya still a lot of data loss, data ordering, receiving, and expenditures are still not recorded properly.To solve the above problems, the storage and data recording of raw materials need to be converted into digital data and computerized form. To meet these needs, the application needs to be made on the production of raw material procurement Sablon Garment Surabaya. Stages of making this application begins with communication, planning, modeling, construction, and operation. Once tested, the application of the procurement of raw materials for production can produce digital data in the form of data of raw materials, supplier data, employee data, city data, the data for the brand, administrator data, ordering data, data on revenues, expenditures data, reports reservations, reception reports, expense reports and statement of changes in stock. Keywords: Keywords: Applications, Raw Materials Procurement, Raw Materials Booking.